Pengaruh terapi akupresur menggunakan alat pijat kayu dan minyak zaitun terhadap perubahan tekanan darah pada penderita hipertensi - Ni Made Merry Wedani; Riska Oktalina; Sujiah Sujiah (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Hypertension is a non-communicable disease with a high prevalence that carries the risk of serious complications such as heart disease, stroke, and kidney failure. Non-pharmacological therapies, such as acupressure, serve as alternatives for blood pressure control. This study aims to determine the effect of acupressure therapy using a wooden massage tool and olive oil on blood pressure changes in hypertensive patients at the Kedaton Community Health Center in 2025. Purpose: To determine the effect of acupressure therapy using a wooden massage tool and olive oil on blood pressure changes in hypertensive patients. Method: This study employed a quasi-experimental design with a two-group pre-test post-test approach. The sample consisted of 52 respondents divided into intervention and control groups. Blood pressure was measured before and after the intervention. Data analysis was performed using the Wilcoxon Signed-Rank test and the Mann-Whitney test. Results: The results showed a significant decrease in systolic and diastolic blood pressure in the intervention group (p<0.05), as well as a significant difference between the intervention and control groups. Conclusion: Acupressure therapy using a wooden massage tool and olive oil has a significant effect on lowering blood pressure and can be utilized as a complementary therapy. Keywords: Acupressure; Blood Pressure; Complementary Therapy; Hypertension.